2021
DOI: 10.3390/sym13122348
|View full text |Cite
|
Sign up to set email alerts
|

Lower Limb Perfusion Asymmetries in Humans at Rest and Following Activity—A Collective View

Abstract: The significance of lower limb perfusion asymmetries remains unknown in healthy individuals. Our study aims to understand how factors such as posture, sex, age, and body weight relate to perfusion. Data from studies previously published by our group, including experiments using laser Doppler flowmetry as the gold standard for perfusion measurements in baseline, (various) challenge, and recovery phases was assembled from a total of 139 healthy participants. Body position was shown to be a primary determinant of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
3
3
0
Order By: Relevance
“…Pathological blood perfusion differences in lower limbs are known [33][34][35]. This unevenness has also been described in the absence of disease and has been related to age, sex and BMI [6,11,12,29]. Thus, the interlimb asymmetries here detected were expected.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Pathological blood perfusion differences in lower limbs are known [33][34][35]. This unevenness has also been described in the absence of disease and has been related to age, sex and BMI [6,11,12,29]. Thus, the interlimb asymmetries here detected were expected.…”
Section: Discussionsupporting
confidence: 60%
“…Our group's research has been focused in understanding these physiological perfusion asymmetries in the lower limb, including distal microcirculatory adaptive mechanisms prior and after movement [8,12,[27][28][29]. In the present paper, we explore these themes further by studying potential relationships among perfusion and plantar pressure variables in the feet of a healthy group of young participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, our findings do not necessarily contradict the results of Fahs et al, who certified the influence of leg dominance on local vascular function, as this study did not investigate perforator quantity our quality (Fahs et al, 2014). The same applies to the study of Rodrigues et al, who assessed foot blood perfusion by laser Doppler flowmetry and found higher blood flow in dominant legs (Rodrigues et al, 2021).…”
Section: Fat and Muscle Thickness On Dominant And Nondominant Legssupporting
confidence: 70%
“…Yet, our findings do not necessarily contradict the results of Fahs et al, who certified the influence of leg dominance on local vascular function, as this study did not investigate perforator quantity our quality (Fahs et al, 2014). The same applies to the study of Rodrigues et al, who assessed foot blood perfusion by laser Doppler flowmetry and found higher blood flow in dominant legs (Rodrigues et al, 2021). By contrast, Kadoguchi et al showed comparable flow mediated dilation on dominant and nondominant popliteal arteries in contrast to increased flow‐mediated dilation of brachial arteries on dominant arms compared to nondominant arms indicating an asymmetry of vascular function in the upper‐, but not in the lower extremities (Kadoguchi et al, 2020).…”
Section: Discussionmentioning
confidence: 71%